2010
DOI: 10.1016/j.neulet.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of intrinsic and extrinsic hand muscle activity as a function of wrist joint angle during two-digit grasping

Abstract: Fingertip forces result from activation of muscles that cross the wrist and muscles whose origins and insertions reside within the hand (extrinsic and intrinsic hand muscles, respectively). Thus, tasks that involve changes in wrist angle affect the moment arm and length, hence the force-producing capabilities, of extrinsic muscles only. If a grasping task requires the exertion of constant fingertip forces, the Central Nervous System (CNS) may respond to changes in wrist angle by modulating the neural drive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…4), as well as medial and lateral finger phalanges (Fig. 5), which may show precision gripping or precision handling of objects (Johnston et al, 2010;Landsmeer, 1962;Long et al, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…4), as well as medial and lateral finger phalanges (Fig. 5), which may show precision gripping or precision handling of objects (Johnston et al, 2010;Landsmeer, 1962;Long et al, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Weiss Sign Language alphabet to examine whether muscle synergies could serve as a predictive framework for new hand postures; the synergies identified in this study were generally subject specific. Johnston et al 12 found evidence of synergistic control of extrinsic and intrinsic hand muscles during a two-digit task. These studies generally did not investigate the presence of synergies during the different types of hand movements used in ADLs (with the exception of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…These redundant degrees of freedom allow for an infinite number of solutions when performing whole-hand object manipulation (Zatsiorsky and Latash, 2008). Despite this, the central nervous system (CNS) tends to select certain families of solutions, or synergies, when grasping objects (Santello and Soechting, 2000;Rearick and Santello, 2002;Shim et al, 2003Shim et al, , 2005aJohnston et al, 2005Johnston et al, , 2010Shim and Park, 2007). A better understanding of such control mechanisms can lead to improved rehabilitation of neuromuscular dysfunction (Nowak, 2008;Alberts and Wolf, 2009;Schieber et al, 2009), and the development of more dextrous robotic limbs (Bae et al, 2005;Choi et al, 2008;Lee et al, 2009;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%